Evaluasi Sistem Informasi Perpustakaan STMIK dan Politeknik PalComTech Kerangka Kerja Cobit 4.1 Domain Plan dan Organise - putri, meidyan permata (Teknomatika, 2017)
The purpose of this study to determine whether the library information system has been in accordance with COBIT 4.1 standards. This research is conducted by survey approach in the form of Maturity level measurement with COBIT Framework so that it can get the current position which then can be used to determine the target to be achieved. The result of this research is maturity level using COBIT Framework on Domain Planning / Organization (PO) at level 2.55 indicates that in implementing information technology governance has done standardized procedure, documented, and have communicated through training and media.Kata Kunci : Evaluation,Â  Framework Cobit, Maturity Level